Greener Limonade - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
The environment is greener now in the Limonade area of northern Haiti, thanks to a reforestation programme by the World Food Programme (WFP) and the Ministry of Agriculture. WFP donated seeds and 30,000 plastic gro-bags, and the Ministry provided...